Matrix [large type] : a novel - Groff, Lauren (Random House Large Print, 2021)
Cast out of the royal court, seventeen-year-old Marie de France, born the last in a long line of women warriors, is sent to England to be the new prioress of an impoverished abbey where she vows to chart a bold new course for the women she now leads and protects.